Entre nóias, playboys e a galera da vila: uma etnografia das relações sociais entre jovens na periferia de Paranaguá PR - Leite, Tiago Pereira (2012)
This dissertation is the final of a research that had as conjecture the necessity of research of social practices and dynamics of youth in the urban periphery. From the fact that there is a polyphony of meanings to youth generation, the objective was relate the many ways of to be young and the experience of live in the periphery. The central question of research was what place the periphery´s life has as source of life experiences ? The method of research was the ethnographic, observing the ways of interation of youngs, their practices, values, relationships and representations of themselves and the otherness. The field research was the Parque São João, a neighborhood situated in the periphery of Paranaguá city, Paraná state, Brazil. The fieldwork was made in two phases: the first last almost one month and had the aim of to develop the research project. The second phase last three months and made an observation of the young people in their daily social interaction, mostly in a corner of the neighborhood. The results achieved by the crossing between the concepts of youth and periphery , and related with social experience , did show that the young people create relations with many symbols and meanings, thinking about the ways of live in the neighborhood, that was seen either as a place of bad people and as a our place . It is important also the necessity of playing os social stigma of to be a poor young living in the periphery, which produces a dual sight of world, marked by pairs of opposition as rich versus poor , playboy versus vida loca , periphery versus core. So, in this dynamic context, the young people build their identities , being important the presence of local context. The presence of drugs also appeared, as source of experiences to young people. The drugs universe creates the group hierarchy and the male ethos, related to the native concept of vida loca . At last, it were used the categories as cenário , pedaço , mancha and circuito , developed by Magnami (2005) and it was possible demonstrate, by ethnography of a leisure night, that the young people make few movement by the city, standing in their neighborhood leisure spaces. However, the local context do not prevent that the young people to live the otherness experience, what occurs when they go to a gas station around the neighborhood and when they consume famous fashion clothes.